006 Translating Knowledge Into Practice: A Systematic Review Of Barriers, Facilitators And Interventions Impacting On Uptake Of Systematic Reviews. (15th August 2013) - Wallace, J; Byrne, C; Clarke, M
Abstract : Background: The increased uptake of evidence from systematic reviews is advocated because of their potential to improve the quality of decision making for patient care and their use in clinical practice guidelines. Objectives: To identify how uptake of evidence from systematic reviews can be enhanced. Methods: Data sources : We searched 19 databases covering the full range of publication years. Study selection : Studies of barriers and natural facilitators to uptake of evidence from systematic reviews and meta-analyses were eligible. These studies encompassed survey, focus group and interview designs. Intervention, or outcome, studies were also included. Data extraction : Two reviewers independently assessed quality and extracted data that were summarised and then analysed. Using a pre-established taxonomy, the barriers and facilitators were organised into a framework according to their effect on knowledge, attitudes, or behaviour. For the intervention studies, two reviewers also independently assessed quality and extracted data. Data synthesis : Twenty-seven studies dealing with barriers were detected and 15 studies that included investigation of natural facilitators. Ten publications addressing interventions met inclusion criteria. A synthesis of findings was conducted to find out to what extent the interventions overcome the perceived barriers and built on the facilitators detected. Results: Educational visits, summaries of systematic reviews, and targeted messaging had a significant impact on systematic review uptake and also addressed a range of identified barriers and facilitators. Conclusion: On the basis of this study, specific strategies addressing a range of barriers and facilitators are recommended to enhance uptake of systematic reviews and meta-analyses. Promising interventions are also identified.